Bibliotekininkas moksliinkas Kazys Sendzikas - Raguotienė, Genovaitė (Knygotyra, 1996)
Two articles discuss the research of Kazys Sendzikas (1909?-1940) on Lithuanian libraries and the history of the period of the Republic (1918-1940). First, the author reviews Sendzikas’s written heritage, which consists of 20 items. These are mainly articles on Lithuanian library history, particularly on the Library of the Kaunas Priests’ Seminary. K. Sendzikas prepared publications from the archives and manuscripts departments on Lithuanian books and authors of the first half of the 19th century. These materials cover famous cultural, library, and book workers such as M. Valančius, J. K. Gintila, J. A. Pabrėža, B. Šmigelskis, and others. The author analyzes Sendzikas’s studies on parish libraries, reading, and archives. The biography of K. Sendzikas has not been investigated until now. Although he lived at the beginning of the 20th century, data about his life is very scarce. The author of the article presents some facts about his life and activities found in archives and other sources. This information reveals that K. Sendzikas lived a short but very complex, dramatic, mysterious, and even tragic life. K. Sendzikas made a fruitful contribution to the fields of library and book science in a very short time of 3.5 years (1937-1940.06.). His works have great historical and contemporary value for modern research.